Students' sensory modalities and acceptance of using funancial.s.battle (FSB) as learning method in accounting education / Syahida Md Zeni... [et al.] - Md Zeni, Syahida; M Yacob, Noor Hasimah; Azis, Saflina; Mat, Mustafa Kamal (Universiti Teknologi MARA Cawangan Pahang., 2019)
Accounting educators uses various techniques in making the subject interesting including introducing of accounting games in class. However, previous study shows that students’ improvement is varied. Therefore this paper aims to explore students' ability to absorb learning financial statement using board game known as FUNancial.S.Battle (FSB) with their sensory modalities, VAK (visual, auditory, kinesthetic). 64 students enrolled for Financial Accounting 2 (FAR160) subject was chosen to participate in this study, as they have enough basic knowledge about financial statement. They were given set of Neuro Linguistic Programming (NLP) representational system preference test before playing the FSB game, once finished, another set of questionnaire was given to get their feedback about the game. Results were then analysed using SPSS to find whether there is any relationship between students' VAK and their acceptance of using board game as learning method in understanding the preparation of financial statement. Result shows that students with kinesthetic ability preferred using games better than the others. Since this area of study was rarely found in Malaysia, further study need to be done to confirm the finding. Furthermore sample of students should involve those majoring in accounting and also non-accounting students to see the difference. Further analysis should be done in future research to find out the significant relationship between sensory modalities and FSB game acceptance.